If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 4 = -1(x + -3) Reorder the terms: 4 + -2x = -1(x + -3) Reorder the terms: 4 + -2x = -1(-3 + x) 4 + -2x = (-3 * -1 + x * -1) 4 + -2x = (3 + -1x) Solving 4 + -2x = 3 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 4 + -2x + x = 3 + -1x + x Combine like terms: -2x + x = -1x 4 + -1x = 3 + -1x + x Combine like terms: -1x + x = 0 4 + -1x = 3 + 0 4 + -1x = 3 Add '-4' to each side of the equation. 4 + -4 + -1x = 3 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 3 + -4 -1x = 3 + -4 Combine like terms: 3 + -4 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| 4(x-5)=8x-6 | | 4(x-2)+(2x+3)=6 | | 0=2x^2+4x-1 | | x^4-3.75x^2-1=0 | | 7.1=X-6.5 | | 104=4(5)(4)+2(4)h | | X/3=6q-24 | | 15+3(4b-2z)=5z-2b | | logX1/64=-2 | | X-77=-9x+113 | | 15+3(4z-2b)=5b-2z | | S/107=100 | | 7(x+4)-3(x+6)=19 | | 2x+(3x-4)=(2x-3) | | 1+(1)(1)= | | (1)(1)+1= | | 9x-7=-3x+29 | | -1.4121-(1-2.4)= | | 4+(2)(3)= | | 4(2+3)= | | 7x-14=-3x+6 | | 3(x-1)(x+1)=9 | | 7+(1)(-2)= | | 7(1)+(-2)= | | 7(1+-2)= | | 3(2x-1)=4(x+2) | | 7(7x-2)=49x-14 | | -5+2(4)= | | -5(2)+4= | | y-4=-2/3x | | -5(1-2n)=15 | | -5(2+4)= |